Comparative proteomic analysis to characterize temperature-induced viable but non-culturable and resuscitation states in Vibrio cholerae. Issue 7 (24th May 2019) - Debnath, Anusuya; Mizuno, Tamaki; Miyoshi, Shin-ichi
Abstract : Vibrio cholerae can survive environmental adversities by entering into a viable but non-culturable (VBNC) state and is able to resuscitate under favourable conditions. In this study, an environmental strain of V. cholerae (AN59) showed a decrease in culturability from 4×10 7 to ≤ 3 c.f.u. ml –1 in artificial seawater media at 4 °C within 35 days. During the course of VBNC progression, viability was confirmed by real-time RT-PCR which showed reduced but stable expression of molecular chaperones groEL and dnaK . Resuscitation was induced in VBNC microcosm by a temperature increase from 4 to 37 °C for 24 h. The results obtained from resuscitation and growth experiments suggest that 10 3 –10 4 c.f.u. ml –1 of VBNC cells should recover upon temperature increase and grow to attain 10 7 c.f.u. ml –1 . We used comparative proteomics to differentiate recovery from the VBNC state and selected 19 proteins whose expression was significantly variable between these two states. These proteins were mainly related to carbohydrate metabolism, phosphate utilization, stress response, transport and translation. The main difference in the proteome profile was higher protein expression in the recovery state compared to VBNC state. However, during recovery Pi-starvation led to expression of PhoX, PstB and Xds, which might help in utilization of extracellular DNA to promote growth after resuscitation. In addition, the expression of EctC suggests that osmotic adaptation is necessary to grow at high salinity. Detection of AhpC in the VBNC and recovery state indicates the significance of the oxidative stress response. A temperature-induced VBNC and recovery state is a combination of adaptive and survival responses under nutrient limitation.